The Impact of Modeling Instruction Based on System Toward Work-Energy Concept Understanding - Zainul Mustofa; Sutopo Sutopo; Nandang Mufti; Anik Asmichatin (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This study aimed to explore the effectiveness of modeling instruction based on a system for improving student’s understanding of energy concepts on high school students. This Research was a mixed-method design with an embedded experimental model. The subject of this study was the 62 students of 11th grade, at Senior High School in Nganjuk, Indonesia. Modeling instruction based on system learning could significantly improve students' understanding of concepts better than conventional learning. Based on the calculation of the effectiveness of learning using N-gain obtained for 0.33 (medium or low medium category) for the treatment class and 0.18 (low category) for the control class. It concluded that improved students' conceptual understanding of the treatment class was better than the control class. This research also was identified student’s difficulties especially in differentiating forces and work. Students propensity to use p-prime in solving problems rather than using energy theorems.